International Experience of Legal Regulation of Social Vacations - V. O. Latysheva (Law and Safety)
The author of the article has studied international and legal acts that envisage the norms that provide social vacations for employees. The author has analyzed experience of legal regulation of social vacations in the USA, the countries of the European Union, the countries of the former Soviet Union, etc.